Navigating the Implementation of the Merdeka Curriculum in EFL Classrooms: Challenges and Pedagogical Needs in Madrasah Contexts - Restika, Yesa; Maisarah, Ira (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
This study examines the challenges and pedagogical needs experienced by EFL teachers in implementing the Merdeka Curriculum within a madrasah context in Indonesia. While the Merdeka Curriculum promotes student-centered, flexible, and project-based learning, empirical evidence on its implementation in Islamic senior high schools remains limited. Adopting a qualitative case study design, this research draws on in-depth interviews with two experienced English teachers at an Islamic senior high school in Indonesia to capture their lived experiences during the curriculum transition. The findings identify four interrelated categories of challenges: instructional challenges, including low student motivation and difficulties in addressing mixed-ability classrooms; resource-related constraints, particularly limited access to curriculum-aligned teaching materials; assessment-related challenges stemming from uncertainty in designing appropriate learning modules and assessment practices; and institutional support issues, marked by insufficient guidance and systemic backing. In response to these challenges, teachers highlighted the need for sustained professional development, stronger collegial and leadership support, and improved digital infrastructure, including reliable internet access and technological tools. This study argues that the successful implementation of the Merdeka Curriculum depends not only on policy design but also on teachers’ professional readiness and institutional support systems. By foregrounding teachers’ perspectives, this research contributes to the growing literature on curriculum reform in EFL contexts and offers context-sensitive insights for strengthening curriculum implementation in Islamic secondary education.